Biodeinking Kertas Koran Bekas menggunakan Ekstrak Kasar Lakase dari Marasmiellus palmivorus - Sitatun Zunaidah; Rendana Saputra; Sri Harjati Suhardi; Hendro Risdianto (Center for Pulp and Paper, 2021)
Biodeinking of Old Newspaper using Crude Laccase from Marasmiellus palmivorus Abstract Enzymatic deinking is receiving growing attention due to the negative environmental impact caused by chemical deinking. Old newspaper (ONP) is one of the materials that can be used in paper recycling. The use of the crude laccase from Marasmiellus palmivorus in biodeinking is due to its capability to remove the ink. The objective of this research was to determine the potential use of laccase in enzymatic deinking to increase the brightness value and reduce ERIC (Effective Residual Ink Concentration) value on old newspapers. Laccase was produced from M. palmivorus by using cultivation in a static Solid State Fermentation (SSF) reactor with lignocellulosic as substrate. The methodology involves the production of crude laccase extract, laccase optimization using variations of dosage, temperatures, and times. The highest laccase activity is 1,142.86 U/L (16 U/mg). Optimization of laccase crude extract enzyme in biodeinking can increase brightness values by 15.22% (54.27 %ISO) to 25.03% (58.89 %ISO) compared to controls (47.09% ISO) and reduce ERIC values by 46.12% (452.1 ppm) to 68.26% (266.4 ppm) compared to control (839.2 ppm). Keywords: biodeinking, Marasmiellus palmivorus, laccase, old newspaper Abstrak Deinking enzimatis semakin mendapat perhatian karena dampak negatif terhadap lingkungan yang disebabkan oleh deinking secara kimia. Kertas koran bekas merupakan salah satu bahan yang dapat didaur ulang. Pemanfaatan ekstrak kasar lakase dari Marasmiellus palmivorus digunakan dalam biodeinking karena memiliki kemampuan untuk menyisihkan tinta. Penelitian ini bertujuan untuk mengetahui potensi ekstrak kasar lakase untuk meningkatkan nilai brightness (derajat cerah) dan menurunkan nilai Effective Residual Ink Concentration (ERIC) dalam proses biodeinking kertas koran bekas. Produksi ekstrak kasar lakase dilakukan dalam reaktor statis Solid State Fermentation (SSF) dengan substrat material lignoselulosik. Produksi ekstrak kasar lakase menghasilkan aktivitas tertinggi 1.142,86 U/L (8,33 U/mg). Perlakuan biodeinking dengan enzim ekstrak kasar lakase dapat meningkatkan nilai derajat cerah 15,22% (54,27 %ISO) sampai 25,03% (58,89 %ISO) dibandingkan dengan kontrol (47,10 %ISO) dan menurunkan nilai ERIC 46,12% (452,1 ppm) sampai 68,26% (266,4 ppm) dibandingkan dengan kontrol (839,2 ppm). Kata kunci: biodeinking, Marasmiellus palmivorus, lakase, kertas koran bekas